Retinoid and rexinoid signaling: methods and protocols - Ray, Swapan K. (Methods in molecular biology, 2019)
Proteomics to Predict Loss of RXR-γ During Progression of Epithelial Ovarian Cancer -- Targeting Non-Genomic Activity of Retinoic Acid Receptor-Gamma by Acacetin -- Lentiviral Mediated shRNA Approaches: Applications in Cellular Differentiation and Autophagy -- Ligand Design for Modulation of RXR Functions -- In Vitro Models to Study the Regulatory Roles of Retinoids in Angiogenesis -- Analysis of Retinoic Acid Receptor Signaling in Colorectal Cancer -- Methods to Assess Activity and Potency of Rexinoids using Rapid Luciferase-Based Assays: A Case Study with Net-TMN -- Methods to Generate an Array of Novel Rexinoids by SAR on a Potent Retinoid X Receptor Agonist: A Case Study with Net-TMN -- Promoting Primary Myoblast Differentiation through Retinoid X Receptor Signaling -- Mapping Retinoic Acid-Dependant 5mC Derivatives in Mouse Embryonic Fibroblasts -- Hemodynamics-Based Strategy of Using Retinoic Acid Receptor and Retinoid X Receptor Agonists to Induce MicroRNA-10a and Inhibit Atherosclerotic Lesion -- Evaluating the Role of RARβ Signaling on Cellular Metabolism in Melanoma Using the Seahorse XF Analyzer -- Highly Sensitive Quantitative Determination of Retinoic Acid Levels, Retinoic Acid Synthesis, and Catabolism in Embryonic Tissue Using a Reporter Cell-Based Method -- A Behavioral Assay to Study Effects of Retinoid Pharmacology on Nervous System Development in a Marine Annelid -- Retinoic Acid as a Modulator of Proximal-Distal Patterning and Branching Morphogenesis of the Avian Lung -- Translation of Chemopreventive Effects of Retinoids and Rexinoids: Extraction and Quality Assessment of RNA form Formalin-Fixed Tissues -- Assessing Autophagy during Retinoid Treatment of Breast Cancer Cells -- Non-Radioactive and Radioactive Telomerase Assays for Detecting Diminished Telomerase Activity in Cancer Cells after Treatment with Retinoid